Exploring the unmet needs of family caregivers of cancer patients in Southwest Nigeria - P.O. Amoo; N. Busisiwe (International Journal of Africa Nursing Sciences, 2025)
Background: Cancer imposes a significant burden on family caregivers in low-resource settings like Southwest Nigeria, where financial strain, limited information, and emotional distress are prevalent but often unaddressed. Understanding these unmet needs is vital for enhancing caregiver support and patient outcomes. Purpose: This study aimed to explore the unmet needs of family caregivers of cancer patients in Southwest Nigeria and evaluate the adequacy of information provided for effective caregiving. Methods: An ethnographic approach was employed, involving semi-structured interviews, focus group discussions, and ethnographic observations. Data were collected from 35 caregivers across multiple hospitals and home settings in Southwest Nigeria over six months and analysed using thematic analysis with NVIVO version 12. Results: findings showed that majority of the caregivers are female 60 %, mean age 39.6 years, key unmet needs included financial strain due to high treatment costs (reported by most participants), insufficient information about cancer and caregiving (lack of guidance on patient care), emotional and psychological stress (distress from patient suffering), inadequate support from healthcare providers (poor communication), and social isolation exacerbated by misconceptions about cancer contagiousness. Caregivers emphasised the need for transparent communication, financial aid, and emotional support. Conclusion: This study underscores the critical unmet needs of family caregivers in Southwest Nigeria, highlighting the necessity for improved communication, financial assistance, and psychosocial interventions. Policy changes are essential to recognize caregivers as integral to cancer care. Future research should investigate tailored intervention models for diverse settings.